Impact of environmental conditions on the early growth of the endangered Korean fir (Abies koreana E.H.Wilson): insights for conservation and restoration strategies - Jae-Hyun Park; Han-na Seo; Jingyu Han; Chanwoo Park; JunHo Park; Hyo-In Lim (Forest Science and Technology)
Environmental factors are crucial elements that significantly influence the growth and development of plants. This study investigated the impact of environmental conditions (light, air temperature, air humidity, etc.) on the early growth of juvenile Korean fir (Abies koreana E.H.Wilson). Using random forest models and scatterplot matrix analyses, we examined the complex relationships between juvenile Korean fir early survival and various environmental factors. Specifically, a one-way ANOVA was conducted to assess the impact of light regulation in shading experiments on the growth of Korean fir seedlings. Additionally, a t-test was performed to compare the growth differences of Korean fir seedlings in two restoration sites with different canopy coverages. The results confirmed that light conditions significantly affect the growth of Korean fir seedlings, with better early growth observed in shaded conditions compared to full sunlight. Furthermore, field restoration site surveys indicated that the growth of height and root collar diameter of restored Korean fir seedlings was better in areas where the canopy coverage of the existing forest was between 60% and 75%. These findings suggest that the prerequisite for the restoration of the endangered Korean fir seedlings is the achievement of optimal light conditions during the early establishment phase.